Evaluation of the Knowledge, Awareness, Attitude, and Performance of Radiographers regarding Adherence to Radiation Protection Principles in Iran - Hassan Zarghani; Masoud Jabbari; Sajjad Pandesh (Tehran University of Medical Sciences, 2024)
Background and Aim: X-ray radiation, besides its useful applications in the diagnosis and treatment of diseases, also has harmful effects. With the increasing demand for various radiographs and X-ray imaging, radiation protection for radiographers is of particular importance. In this regard, a study was conducted to examine the level of awareness, attitude, and performance of radiographers in Iran with regards to the effects of ionizing radiation and protective methods against them. Materials and Methods: In this descriptive-analytical study, based on a census, the awareness, attitude, and performance of radiographers in 52 cities in Iran were examined by using a questionnaire. Data from 847 radiographers were collected. Finally, the data were analyzed using t-test and analysis of variance through SPSS  statistical software. Results: Out of the total distributed questionnaires (748 items), 531 questionnaires were completely filled by radiation workers. In the present study, 46% were male and 53% were female, with average scores related to the awareness, attitude, and performance of radiographers in the field of radiation protection being 59.9, 69.4, and 43.54, respectively. There was no statistically significant difference (P<0.05) between the awareness levels of individuals who had undergone refresher training (24.3%) and those who had not. Radiographers' knowledge of specialized information such as the principle of As Low as Reasonably Available (ALARA) (68.5%), Bucky factor (65.5%), and heel effect (61%), alongside the relationship between source-to-skin distance and radiation intensity (71%), was at a moderate level. Conclusion: The poor performance of radiologists in this study is not solely attributed to functional deficiencies but sometimes also involves the institutionalization of incorrect principles. These weaknesses and shortcomings are undoubtedly the result of inadequate supervision and erroneous modeling over a long period. If not addressed, they will undoubtedly have irreparable destructive consequences in the future, especially with the increasing advancement of diagnostic radiology methods.